Social Media and Change in Psychological Distress Over Time: The Role of Social Causation. Issue 5 (21st June 2019) - Hampton, Keith N
Abstract: This article tests the relationship between information and communication technologies (ICT), such as the Internet, cell phones, and social media, and change over time in psychological distress (PD) and risk of serious psychological distress (SPD) associated with depression and anxiety disorders. Using a longitudinal panel design, survey data from a representative sample of American adults, findings revealed that home Internet and social network site (SNS) use are associated with decreased PD over time. Having extended family who are also Internet users further decreases PD. PD increased or decreased in relation to change in the PD of extended family who also use SNSs. For most people, ICT substantively reduce PD; in rare cases, an extreme spike in PD of extended family also on SNSs, there was a trivial increase to the risk of SPD. PD did not change when extended family not on social media experienced a change in their PD.